Association of socioeconomic factors with body mass index, obesity, physical activity, and dietary factors in Belo Horizonte, Minas Gerais State, Brazil: The BH Health Study - Julia Ward; Amélia Augusta de Lima Friche; Waleska Teixeira Caiaffa; Fernando Augusto Proietti; César Coelho Xavier; Ana V. Diez Roux (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract Obesity prevalence is rapidly increasing in developing countries. Existing research investigating social patterning of obesity and its risk factors in Latin American urban contexts has inconsistent findings. This study analyzed a multistage household survey in adults in Belo Horizonte, Minas Gerais State, Brazil. Marginal models were used to examine the association of education and household and neighborhood income with body mass index (BMI), obesity, physical inactivity, and low fruit and vegetable intake after adjusting for age and ethnicity and stratifying by sex. BMI and obesity were inversely associated with education in women. BMI was positively associated with household and neighborhood income in men. Additionally, physical inactivity and low fruit and vegetable intake were inversely associated with education and household income in both men and women, and physical inactivity was inversely associated with neighborhood income in men. Understanding the drivers of these patterns will allow for development of appropriate policy and interventions to reduce cardiovascular disease risk in large cities in Latin America.